Debris accumulation, acoustic and wear analysis of compression ignition engine using bio alcohols blends - Solangi, Faheem Ahmed; Ansari, Ali Murtaza; Noonari, Altaf Alam; Hussain, Fayaz; Zhang, Bo; Nawi, Nazmi Mat; Saleel, C Ahamed (Elsevier BV, 2025)
The use of alternative fuels in diesel engines has become increasingly important in recent years. In this study, deposit development was examined using combinations of n-pentanol, diesel, and gutter oil. Finding out how well adding n-pentanol improves ternary blend performance is the aim of this study. Three test fuels—DF, DF95GO5, and DF70GO20Pn10—were chosen for this purpose. Each fuel sample underwent a separate engine test to examine the surfaces of the piston crowns. The SEM and EDX tests revealed that using DF95GO5 significantly altered the piston's surfaces. The gutter oil binary mix fuel was found to produce carbon deposition more quickly than diesel fuel, with 67.68 % for GO and 60.72 % for D100. However, engine part deposition decreased when 1-pentanol was combined with gutter oil instead of diesel fuel, even though n-pentanol had a 52.90 % deposition rate. To compare to DF, N-pentanol was added as a ternary blend DF70GO20Pn10 for copper (Cu), nickel (Ni) 0.37 ppm, and cadmium (Cd) 8 ppm. The ternary blend gasoline, on the other hand, contained less debris. The results showed that engine noise emissions were generally increased when gutter oil was added to DF95GO5 diesel fuel. However, DF70GO20Pn10 had less of an effect on the engine's noise emissions (86.63 dB) than baseline fuel and gutter oil blend.